PEMBINAAN MENTAL SPIRITUAL KRISTEN WARGA BINAAN DI LAPAS KELAS IIA CIKARANG - Ernawaty Tampubolon; Joko Prihanto (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
This paper departs from the problem of the role of God's servant/church servant in fostering the spiritual mentality of God's congregation, in this case, the inmates of Lapas IIA Cikarang. The biggest fear of inmates while serving their sentence is being away from their families. Servants of God who devote themselves to fostering inmates should also equip themselves to serve the mental recovery of inmates. Spirituality impacts the good and bad of individual behaviour in interacting with God and others, influenced by the environment, experience and knowledge. New thoughts and enthusiasm and facing the realities and challenges of life more religiously. Dare to reject negative thoughts that tempt them to return to his dark life of committing crimes. Christian Spirituality Mentality also helps His congregation find wholeness and balance in their relationship with God, others, and nature. Encouraging motivation, solidarity, dialogue and cooperation in building a just, peaceful and dignified life. Mental Spiritual Guidance is an effort to improve and renew the actions and behaviour of inmates through mental guidance of their souls and spirituality so that they become inmates who have a solid spiritual faith and healthy personality, reflect the character of Christ and are responsible for living their lives while in prison, furthermore, later, after being free and returning to society.